Sudden infant death syndrome (SIDS) and the routine otoacoustic emission infant hearing screening test: an epidemiological retrospective case–control study. Issue 7 (18th July 2019) - Blair, Peter S; Rubens, Daniel; Pease, Anna; Mellers, Diane; Ingram, Jenny; Ewer, Andrew K; Cohen, Marta C; Sidebotham, Peter; Ward Platt, Martin; Coombs, Robert; Davis, Adrian; Hall, Amanda; et al.
Abstract : Objectives: To investigate whether decreased otoacoustic emission (OAE) signal recordings in the right ear are associated with an increased risk of sudden infant death syndrome (SIDS) and to monitor any temporal changes in risk factors. Design: Retrospective case–control study. Setting: Telephone interviews with families recruited in England between July 2016 and October 2017 who experienced the unexpected death of a child <4 years old since 2008 and control families recruited from maternity wards in Bristol and Birmingham. Participants: We recruited 91 (89%) of the 102 bereaved families who made initial contact, 64 deaths were under 1 year (sudden unexpected death in infancy) of which 60 remained unexplained (SIDS). Of the 220 control families, 194 (88%) follow-up interviews were conducted. We had analysable hearing data for 24 SIDS infants (40%) and 98 controls (51%). Results: OAE signals were marginally increased rather than decreased among SIDS infants for the right ear, especially at lower frequencies, but not significantly so. The strongest predictors of SIDS were bed-sharing in hazardous (infant sleeping next to a carer who smoked, drank alcohol or slept on a sofa) circumstances (35% vs 3% controls, p<0.0001), infants found prone (33% vs 3% controls, p<0.0001) and infants whose health in the final week was 'not good' (53% vs 9% controls, p<0.0001). The prevalence of maternal smoking during pregnancy among both SIDS mothers (20%) and controls (10%) was much lower than previous studies. Conclusions: Hearing data were difficult to obtain; larger numbers would be needed to determine if asymmetrical differences between the right and left ear were a marker for SIDS. A national prospective registry for monitoring and a renewed campaign to a new generation of parents needs to be considered underlining the initial message to place infants on their backs for sleep and the more recent message to avoid bed-sharing in hazardous circumstances.